1984
DOI: 10.1111/j.1423-0410.1984.tb01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Levels of Serum IgA in Individuals with Selective IgA Deficiency

Abstract: Monitoring of donors with selective IgA deficiency, i.e., with less than 0.5 mg IgA/l, led to the observation that serum IgA levels wer not constant. Small but significant fluctuations in IgA levels were noted (coefficient of variance: 143%) which were greater than the variability inherent in the testing methodology (coefficient of variance: 10%). These fluctuations created difficulties in terms of defining IgA-deficient blood products and had implications with respect to the mechanisms involved in IgA deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 19 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…The fluctuation in IgA levels in these subjects within a 6-month period was an unexpected finding, with four of the original twelve showing normal values on repeat testing. Only one longitudinal study of IgA levels has been reported [22], and the authors found a degree of fluctuation in IgA level which was greater than the variability inherent in the methods used for testing. The findings in this study confirm this, and indicate that caution is required in labelling individuals as IgA-deficient.…”
Section: Discussionmentioning
confidence: 96%
“…The fluctuation in IgA levels in these subjects within a 6-month period was an unexpected finding, with four of the original twelve showing normal values on repeat testing. Only one longitudinal study of IgA levels has been reported [22], and the authors found a degree of fluctuation in IgA level which was greater than the variability inherent in the methods used for testing. The findings in this study confirm this, and indicate that caution is required in labelling individuals as IgA-deficient.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that the serum levels of IgA in individuals with selective IgA deficiency are fluctuating. 21,22 On this background, Laschinger and coworkers 21 recommended that every single donation of fresh-frozen plasma to be used for IgA-deficient patients should be quantified for IgA. Koskinen and coworkers 22 ascribed the fluctuations to methodologic and biologic variations at levels close to the detection limit of the method.…”
Section: Discussionmentioning
confidence: 99%
“…IgA-deficient plasma or cryoprecipitate must be obtained from IgAdeficient donors. Although the IgA concentration in blood components that can be tolerated by patients with anti-IgA is unknown, it is recommended that IgAdeficient donors have serum IgA levels less than 0.05 mg/dL [18].…”
Section: Discussionmentioning
confidence: 99%